KEGIATAN PENGAWASAN HUTAN LINDUNG BUKIT BETABUH DI KABUPATEN KUANTAN SINGINGI - Hermagita Utari Gunawan; Hasim As’ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Forestry supervision is intended to trace and evaluate the implementation of forest management, so that the objectives can be maximally achieved and at the same time provide feedback for further improvement and refinement of forest management. The government and regional governments are obliged to carry out forest supervision and the community also plays a role in forest monitoring. In carrying out supervision, the Government and Regional Governments have the authority to monitor, request information and conduct examination of the implementation of forest management. The current condition of the forest, especially the Bukit Betabuh Protected Forest in Kuantan Singingi Regency, is very alarming, marked by the decrease in the area of the Bukit Betabuh Protected Forest area (66.7% damaged), and an increase in forest damage due to illegal logging, mining, clearing and land grabbing for cultivation. and plantations without permits. The purpose of this study was to determine the monitoring activities of the Bukit Betabuh Protected Forest in Kuantan Singingi Regency and to find out what are the factors that hinder the monitoring of the Bukit Betabuh Protected Forest in Kuantan Singingi Regency. The theory used in this research is the implementation of supervision according to Sondang P. Siagian. To answer this problem, the researcher used a qualitative approach with a case study method and was descriptive in nature. In this study the authors used data collection techniques in the form of interviews, observation and documentation then analyzed based on research problems. The results of this study indicate that the monitoring activities of the Bukit Betabuh Protection Forest in Kuantan Singingi Regency have not been running optimally. Inhibiting factors in conducting forest monitoring include the lack of forest protection personnel, and the mismatch between facilities and infrastructure and the area of protected forest. Keywords: Surveillance, Protected Forest, Direct Supervision, Indirect Supervision.